Islamic bank financing behaviour : a preliminary study / Mohd Afandi Abu Bakar ... [et al.] - Abu Bakar, Mohd Afandi; Abdul Kader, Radiah; Zakaria, RozaHazli; Wahid, Hairunnizam; Mohd Harun, Mohd Fauzi (2012)
This study empirically examines the behaviour of Islamic bank financing activities to the fluctuations in the macroeconomics environment. An unbalanced panel data analysis was employed on 24 Islamic bank institutions' annual data growth from various countries for the period within the span of 1998-2008. Bank micro data such as the total financing, reserve and loan loss provision are used to determine the behaviour after controlling for banks' specific characteristics. The finding shows that Islamic bank financing operations is not tied to the changes in the real GDP growth that makes it more stable and resilient. The bank's reserve and loan loss provision manage to play its role to mellow down the Islamic bank financing behaviour and act as banks' buffers to protect the institutions from the fluctuations in the macroeconomics environment. The finding shows that the bank total financing growth is stronger during strong economic growth and weakens when economic is weaker. Though the degree of association is low as opposed to the GDP growth and the buffers policy that is positively associated to it, the institutions need to be more careful so that over-financing of fixed rate financing can be avoided. The empirical finding suggests that the Islamic bank should go for more into the profit and risk sharing to avoid any unwelcome results from the fixed rate financing instrument.